KECERDASAN EMOSIONAL DALAM PERSPEKTIF AL-QUR’AN - Bagas Ilham Yudhiyantoro; Muhammad Juliansyah (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2022)
The purpose of this study was to determine Emotional Intelligence in the Perspective of the Qur'an. This research uses library research method. Books and scientific journals related to Emotional Intelligence in the Perspective of the Qur'an are references in the work of this paper. The result of this research is an explanation of emotional intelligence from a general point of view and in the perspective of the Qur'an which is useful for every reader to better recognize the emotional side that is in him, and to recognize more in perspective. The Qur'an is the source of guidance. life for every Muslim. By recognizing more from the point of view of the Qur'an, everything that is done in everyday life related to emotional intelligence can provide more value when we carry out daily activities. Factors that affect emotional intelligence, which include family and non-family environmental factors, physical factors, psychological factors, psychological factors, emotional training and education, will better equip us in carrying out daily activities, as well as aspects of emotional intelligence consisting of: : recognizing one's own emotions, managing emotions, motivation, empathy and social skills from the perspective of the Qur'an.